Hallermann–Streiff Syndrome and Lower Limb Lymphedema with Nasal Obstruction - Ana Carolina Pereira de Godoy; Henrique Jose Pereira de Godoy; Jose Maria Pereira de Godoy (Case Reports in Medicine)
Background. Hallermann–Streiff syndrome (HSS) is a rare congenital abnormality involving multiple craniofacial malformations, such as micrognathia, prominent frontal and nasal bones, vision defects, and dental anomalies, which can result in obstructive sleep apnea syndrome. The aim of the present study was to report a case of nasal obstruction in an individual with Hallermann–Streiff syndrome who had never breathed through the nose during treatment for lower limb lymphedema involving cervical lymphatic therapy. Case Report. An 18-year-old female adolescent with a diagnosis of HSS was sent from the genetics service of a teaching school for the treatment of lower limb lymphedema. At around 11 years of age, the patient began to present edema in the left leg, accompanied by broadening of the face and neck. The patient reported having obstructed nostrils and breathing through the mouth her entire life. On the second day of treatment, the patient reported being able to breathe through one of the nostrils, this had never occurred before. Based on this finding, the decision was made to include linear facial lymphatic drainage using the Godoy method, which led to the complete resolution of the nasal obstruction in the first 15 minutes of treatment. Nasal obstruction in children with Hallermann–Streiff syndrome may be caused by lymphedema. Conclusion. A specific lymphatic drainage technique, such as cervical lymphatic therapy and facial linear lymphatic therapy, can resolve the obstruction and maintain the nostrils unblocked for months.